GREEN SYNTHESIS OF SILVER NANOPARTICLES FROM OKRA (ABELMOSCHUS ESCULENTUS) EXTRACT AND THEIR ANTI-DIABETIC EFFICACY IN STREPTOZOTOCIN-INDUCED DIABETIC WISTAR RATS - Ayomide, Theophilus Ajewole; Akintomiwa, Olumide Esan; Babawale, Emmanuel Abiola; Samuel, Oluwaseun Adegbola; Marvellous, Mary Olubode (FUDMA Journal of Sciences, 2025)
Diabetes mellitus is a global healthcare problem that deserves new therapies. Green synthesis of silver nanoparticles (AgNPs) from okra (Abelmoschus esculentus) pod aqueous extract is a new anti-diabetic therapy. This study synthesized and characterized okra-mediated AgNPs and evaluated their anti-diabetic activity in streptozotocin-induced diabetic Wistar rats compared to okra extract and metformin. AgNPs, synthesized by mixing okra extract with 5 mM AgNO3, were identified by UV-Vis spectroscopy (450 nm absorbance), FTIR, XRD, and TEM as spherical nanoparticles (mean 18.01 nm). Thirty-five Wistar male rats were divided into seven groups (n=5): non-diabetic control, diabetic control, and diabetic groups administered okra extract (1 mL/kg), AgNPs (0.2 mL/kg), AgNO3 (1 mL/kg), and metformin (500 mg/kg) via oral gavage for four weeks. AgNPs and okra extract also reduced fasting blood glucose (34.1% and 45.9%, respectively) and HbA1c (up to 65.1%) compared to diabetic controls (p
Keywords: Silver Nanoparticles; Abelmoschus esculentus; Diabetes Mellitus; Anti-Diabetic Activity; Streptozotocin